Birth Control and Pregnancy Management in Pulmonary Hypertension - Olsson, Karen M.; Jais, Xavier (Seminars in Respiratory and Critical Care Medicine, 2013)
Pregnancies in patients with pulmonary arterial hypertension (PAH) are associated with serious complications and mortality rates of more than 50%. Advanced medical therapies for PAH have been developed during the past years resulting in improved hemodynamics, exercise capacity, quality of life, and outcome. However, despite these advances, pregnancy in women with PAH is still associated with excessive maternal mortality. Consequently, all current guidelines strongly discourage pregnancy and recommend an effective method of contraception in women of childbearing age. If this fails, early pregnancy termination is advised. Those patients who choose to continue pregnancy should be treated with targeted PAH therapies including prostacyclin analogues and/or phosphodiesterase type 5 inhibitors. The care of the pregnant women with PAH requires a planned, multidisciplinary approach, preferably in a dedicated pulmonary hypertension referral center, focusing on close monitoring before, during and after delivery.
Keywords: hypertension; pulmonary; pregnancy; right heart failure